URBAN FLOOD RESILIENT LAND USE PLANNING, A CASE STUDY OF SURAT CITY - Arora, Girish; Singh, Kuldeep; Luthra, Ashwani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Disasters and the chances for growth that are brought about by individuals, societies, and nations are closely related. These growth potential lay the foundation for a natural disaster risk disproportion (“UNDP, 2004”). Natural disaster risk used to be primarily caused by human activity in the past. Asia still has a substantially higher level of actual hazard from natural disasters than other continents (“UNDP, 2004”). The role of land governance is very important in determining the overall growth structure and danger of natural disasters. Natural disaster risk vulnerabilities result by unsustainable urban development.